HUBUNGAN KUALITAS UDARA DAN SANITASI RUMAH PENDERITA TB PARU DI WILAYAH PUSKESMAS PEGIRIAN KOTA SURABAYA TAHUN 2015 - Umi Rahayu; Rachmaniyah .; Imam Thohari (Poltekkes Kemenkes Surabaya, 2016)
The problem in this study is the high rate of disease Pulmonary TB, where the disease Pulmonary TB, including contagious, bacteriological quality home air with pulmonary tuberculosisare declining due to sanitary houses, especially covering ventilation, lighting, humidity and densityhousing that does not meet the requirements of home health, Pegirian health center in the area ofSurabaya. The air inside the house that are not fresh in the house can be a media proliferation,among others Mycobacterium tuberculosis bacteria. Such conditions may facilitate diseasetransmission pulmonary TB, which is transmitted from a sick person pulmonary TB to a healthyperson through the air is dropplet issued when the patient coughs, sneezes talk or spit, pollute theair in the house and inhaled by healthy people, then there is pulmonary TB disease transmission. The purpose of this study was to determine the relationship between the bacteriologicalquality of indoor air, house sanitation condition with pulmonary TB disease occurrence in the regionPuskesmas Pegirian Surabaya. The method used in this study is an analytical, cross-sectional, usingChi Square analysis. The population in this study were all patients with pulmonary TB in the regionPegirian Surabaya. Samples are some of the positive pulmonary TB patient population in the regionPuskesmas Pegirian Surabaya 31 patien. Jurnal Penelitian Kesehatan 36 The research variables are bacteriological quality home with pulmonary tuberculosis,Sanitation house include: ventilation, lighting, humidity and residential density and the incidence ofpulmonary TB disease in 2015. The way of collecting data through observation, interviews andlaboratory tests for bacteriological quality of the air in homes with pulmonary tuberculosis Pegirianhealth center region of Surabaya. The conclusion from this study is there is astrong relationship between sanitation house withair quality, in particular ventilation and lighting in homes with pulmonary tuberculosis in HealthCentre Region Pegirian Surabaya.Health Departement to improve environtment sanitationsanitation program home, in the community in order to increse the lighting troght the installation ofglass tiles. Keywords: Quality of air bacteriology, sanitation home, pulmonary TB patients